Insects Functional Morphology, Biomechanics and Biomimetics - Rajabi, Hamed; Gorb, Stanislav N.; Wu, Jianing (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this thematic series, engineers and scientists come together to address two interesting interdisciplinary questions in functional morphology and biomechanics: How do the structure and material determine the function of insect body parts? How can insects inspire engineering innovations?